Characterising the Gut Microbiomes in Wild and Captive Short-Beaked Echidnas Reveals Diet-Associated Changes - Perry, Tahlia; West, Ella; Eisenhofer, Raphael; Stenhouse, Alan; Wilson, Isabella; Laming, Belinda; Rismiller, Peggy; Shaw, Michelle; Grützner, Frank (Frontiers in Microbiology, 2022)
The gut microbiome plays a vital role in health and wellbeing of animals and an increasing number of studies are investigating microbiome changes in wild and managed populations to improve conservation and welfare. The short-beaked echidna (Tachyglossus aculeatus) is an iconic Australian species, the most widespread native mammal, and commonly held in zoos. Echidnas are cryptic animals, and much is still unknown about many aspects of their biology. Furthermore, some wild echidna populations are under threat, while echidnas held in captivity can have severe gastric health problems. Here, we used citizen science and zoos to collect echidna scats from across Australia to perform the largest gut microbiome study on any native Australian animal. Using 16S rRNA gene metabarcoding of scat samples, we characterised and compared the gut microbiomes of echidnas in wild (n=159) and managed (n=44) populations, which were fed four different diets. Wild echidna samples were highly variable, yet commonly dominated by soil and plant-fermenting bacteria, while echidnas in captivity were dominated by gut commensals and plant-fermenting bacteria, suggesting plant matter may play a significant role in echidna diet. This work demonstrates significant differences between zoo held and wild echidnas, as well as managed animals on different diets, revealing that diet is important in shaping the gut microbiomes in echidnas. This first analysis of echidna gut microbiome highlights extensive microbial diversity in wild echidnas and changes in microbiome composition in managed populations. This is a first step towards using microbiome analysis to better understand diet, gastrointestinal biology, and improve management in these iconic animals.